Security assessment of cross-border electricity interconnections. (September 2020) - Beyza, Jesus; Gil, Pablo; Masera, Marcelo; Yusta, Jose M.
Highlights: A framework for assessing the vulnerability & reliability of power grids is proposed. The impact of cross-border interconnections on vulnerability & reliability is studied. The results show that cross-border increase reliability, but also decrease robustness. Abstract: Cross-border electricity interconnections are important for ensuring energy exchange and addressing undesirable events such as power outages and blackouts. This paper assesses the performance of interconnection lines by measuring their impacts on the main reliability and vulnerability indicators of interconnected power systems. The reliability study is performed using the sequential Monte Carlo simulation technique, while the vulnerability assessment is carried out by proposing a cascading failures methodology. The conclusions obtained show that highly connected infrastructures have simultaneously high reliability and limited robustness, which suggests that both approaches show different operational characteristics of the power system. Nevertheless, an appropriate increase in the number and capacity of the interconnections can help to improve both security parameters of the power supply. Seven case studies are performed based on the IEEE RTS-96 test system. The results can be used to help transmission system operators better understand the behaviour and performance of electrical networks.